Syncronization of Certified Intenship Program in the Implementation of Merdeka Belajar and Kurikulum Merdeka - Eko Supraptono; Ulfa Medaty Arief; Henry Ananta; Muhammad Harlanu; Putri Khoirin Nashiro (Journal of Vocational and Career Education, 2022)
The implementation of the Internship program in the context of "Merdeka Belajar” and “Kurikulum Merdeka"  (MBKM) still faces fundamental problems, resulting in activities that have not had the maximum impact, namely the  realization of work readiness, work culture, soft skill competencies and hard skill competencies that are aligned with the  field of study. This study aims to find a formula for synchronizing the internship program that is in line with the independent learning policy (Merdeka Belajar) in preparing apprentice students to face very tight competition entering the job market in the industrial era 4.0. The other objective is to realize several Vocational Education Management Study Center programs. The results of the study from this study center can be developed into a real program to improve the implementation of the MBKM internship. The method used in this research is a qualitative approach. To obtain research data, FGD activities, interviews with IDUKA actors, vocational education experts, the Human Resources Development (HRD) community and related practitioners were used. Data analysis techniques are confirmation, triangulation, and accountability cross checks. The results of the study show that the alignment of the certified internship program is carried out through agreements with partner industries; the number of credit conversions as the right of apprentice students can be achieved by developing a syllabus and study plan that integrates industry needs; the mentoring process is carried out collaboratively between the industrial assistance team and the university.